IMPLEMENTASI KEBIJAKAN PELAYANAN KESEHATAN MASYARAKAT MISKIN DI RUMAH SAKIT UMUM DAERAH KOTA BITUNG - Taalongonan, Etmon; Lengkong, Florence Daicy; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTThis research aims to get an overview or description of the implementation of the policy of the Ministry of health ofthe poor in the HOSPITALS of the city of Bitung. The type of research used in this research is descriptive qualitativeapproach method. Descriptive research aims to describe, summarize a variety of conditions, the situation or thevarious variables that arise in society which became the object of the research. Penelitiaannya focus on the factor ofcommunication, resources, attitudes andbureaucratic structure.Conclusions are in General, almost all indicators of policy implementation services Jamkesmas heldin Bitung city HOSPITALS already are good enough, the indicator of the system/equipment medical facilities arealready full enough. Meanwhile, implementing any policy stance is already pretty good and friendly in serving thepeople who came for the medication, but became the indicator needs to be fixed is the slowness of the distributionof the cards to the general wards of JAMKESMAS recipient JAMKESMAS card.Then there are some factor restricting the achievement of success of implementation of the policy of the Ministry ofhealth of the poor in the HOSPITALS of the city of Bitung IE from external factors, such as lack of understanding ofthe people about the ownership card JAMKESMAS.Keywords: Healthcare, Policy Implementation